Developing tests of successional hypotheses with size-structured populations, and an assessment using long-term data from a Ugandan rain forest - Sheil, Douglas (1999)
In 1947, W. J. Eggeling published an account of forest succession at Budongo, Uganda. This interpretation was based on a large-scale comparative plot study, performed in the 1930s and 1940s. This account, with its implication that species richness declines in late succession, endures as a controversial corner-stone in theories and disputes about community diversity. Data have now been collected over six decades from five of Eggeling's original plots. This paper evaluates Eggeling's successional interpretation of the Budongo vegetation. The first set of analyses assesses the consistency of the original data with the predictions of compositional progression and convergence implicit in Eggeling's model. The second analyses do the same for the time-series observations. A logical approach shows how temporal information may be derived from both between plot, and within plot, evaluations using sizestructured data. A Detrended-Correspondence-Analysis (DCA) of canopy-tree composition, from the original data, ranks the plots in perfect correspondence to Eggeling's successional sequence. A 'development-scoring' procedure is developed using passive-ordination against this sequence; this is then applied to composition by plot and stemsize class. Eggeling's original data are consistent with each prediction assessed. The analyses show compositional progression and apparent convergence across the plot series. and also progression and convergence within each plot. A monodominant-Cynornetra forest is the natural end-point of this progression. The time-series results, though in apparent agreement for one early successional plot, do not generally accord with Eggeling's ideas. The analyses illustrate a general means for evaluating explicit and implicit compositional trends in communities with structured populations.